2021
DOI: 10.1016/j.jamda.2020.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in COVID-19–Positive Nursing Home Residents

Abstract: has had an impact on nutrition at individual, community, national, and global levels. 1 COVID-19 has been associated with weight loss and also has been linked to cachexia and sarcopenia. 2 Anorexia was the most common symptom during COVID-19 infection among patients at an academic long-term chronic care facility, with 70.8% of residents developing anorexia during the illness course. 3 In addition to effects of the disease itself, there are potential unintended consequences of infection control measures. A stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Focusing on the subacute course of COVID-19 in older nursing home residents, Martinchek et all demonstrated that there was a mean weight loss of 4.6% (3.5 kg) in patients with COVID-19 2 months after the onset of COVID-19-related symptoms. 10 It also seems important to mention that preventive restrictions during a local outbreak 10 and general contact restrictions for nursing homes during the pandemic 11 can have a negative impact on the nutritional status including weight loss of COVID-19 negative residents. However, the respective consequences seem to be less severe than in those that have been infected by the coronavirus.…”
Section: The Nursing Home Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the subacute course of COVID-19 in older nursing home residents, Martinchek et all demonstrated that there was a mean weight loss of 4.6% (3.5 kg) in patients with COVID-19 2 months after the onset of COVID-19-related symptoms. 10 It also seems important to mention that preventive restrictions during a local outbreak 10 and general contact restrictions for nursing homes during the pandemic 11 can have a negative impact on the nutritional status including weight loss of COVID-19 negative residents. However, the respective consequences seem to be less severe than in those that have been infected by the coronavirus.…”
Section: The Nursing Home Settingmentioning
confidence: 99%
“…However, the respective consequences seem to be less severe than in those that have been infected by the coronavirus. 10 In this context psychological factors and a lack of mealtime assistance may be of special relevance.…”
Section: The Nursing Home Settingmentioning
confidence: 99%
“…The acute inflammatory response to the infection, which includes marked elevation of inflammatory markers up to the level of cytokine storm, has a high potential to harm a broad spectrum of organs and organ systems [2]. Clinical observation indicates that during the acute phase of infection, lasting approximately 2 weeks, the patient is at risk of losing 5-10% of body weight [3,4]. Although dehydration and muscle loss likely contribute the most to this, the issue has not been elucidated in detail [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Only six studies were performed elsewhere, namely in Canada [7,[22][23][24][25] and South Korea [26]. The number of nursing homes per study varied significantly across studies, ranging from one [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] to 12,576 nursing homes [43]. The number of residents per study ranged from four [27] to 696,310 [44].…”
Section: Types Of Studiesmentioning
confidence: 99%
“…[63,69], the number of outbreaks (N = 1) [23] or temperature (N = 2) [72,76]. One study focused on the impact of COVID-19 on weight loss [41]. Data was mainly collected using swab testing (n = 32, 56%) or electronic health records (n = 21, 37%).…”
Section: Physical Impactmentioning
confidence: 99%